Dissolved carbon monoxide concentration monitoring platform based on direct electrical connection of CO dehydrogenase with electrically accessible surface structure. (February 2020) - Reginald, Stacy Simai; Lee, Hyeryeong; Lee, Yoo Seok; Yasin, Muhammad; Chang, In Seop
Graphical abstract: Highlights: Dissolved CO biosensor platform was developed using DET-based CODH-electrode. Electrical conductivity of CODH cofactor to electrode is key to sensor performance. Electrode surface structure and size affect CODH-electrode proximity and catalytic activity. Au-SRS is a practical support for CODH immobilization. Abstract: CO dehydrogenase (CODH) employed in a dissolved CO biosensor development study harbors a solvent-exposed cofactor capable of DET to electrode. Here, CODH was immobilized on arrays of AuNPs of various dimensions to determine the effect of the size and shape of the electrode surface on the direct electrical connection between CODH and electrode surface. The results showed the degree of proximity between the CODH cofactor and electrode surface, which varied with AuNP size and caused significant changes to the electrical connection at the interface as well as to the substrate accessibility. Consequently, a high-density nanoscale SRS was fabricated on electrode to further facilitate direct electrical connection as well as to enable distribution of CODH into monolayer or near-monolayer for lowering the barrier of CO diffusion toward enzyme. The findings show the feasibility of controlling the direct electrical connection between CODH and the electrode as well as controlling the substrate accessibility.